Peculiarities of planning freestyle wrestling training sessions (Texas Journal of Multidisciplinary Studies, 2022)
The paper considers approaches to automating the construction of training plans for athletes in the sport of freestyle wrestling, as well as the analysis of training plans using a specially developed program "Sport". The data of research work on the macro-structure and mesostructured of training athletes in sports in freestyle wrestling are presented.